Implementing a Pedestrian Tracker Using Low-Cost Bluetooth Inertial Sensors - Bahillo, Alfonso; Arambarri, Ander; Angulo, Ignacio; Onieva, Enrique; Elejoste, Pilar; Perallos, Asier (Ubiquitous Computing and Ambient Intelligence. Personalisation and User Adapted Services, 2014)
Foot-mounted inertial measurement units (IMUs) are becoming the basis for many pedestrian positioning systems as a component of accurate indoor navigation. However, most of solutions that implement low-cost IMUs are often connected to a laptop by a wired connection which interferes with the pedestrian movements. Moreover, nobody walks carrying a laptop but a smartphone. Smartphones are attractive platforms for researchers to collect data coming from several sensors due to their small size, low-cost, and the fact that they are already carried routinely by most people. Therefore, this paper (i) describes a custom-built foot-mounted pedestrian indoor localization system based on commercially available low-cost inertial sensors connected wirelessly (via Bluetooth) to a smartphone, and (ii) demonstrates the capability of smartphones to be used as the target of a wirelessly IMU-based positioning system where raw IMU data will be processed in real time. We have tested the pedestrian tracker with commercial devices in a five floor building with reasonable results (accumulated error lower than 1%).